KEMATANGAN SOSIAL MELALUI KEGIATAN OUTBOUND PADA ANAK USIA 3-4 TAHUN DI PAUD INKLUSI ANGGREK MANDIRI KABUPATEN SITUBONDO - Suyanti Suyanti; Nuriyati Wijarni Nuriyati Wijarni (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2021)
Outbound activities have the function as individual and group therapy for children with problems in motor, emotional and social development. The problem in Anggrek Mandiri Inclusion PAUD institution is that the socialization of children with other people or peers has not been able to develop properly. This study focuses on increasing social maturity through outbound activities for children aged 3-4 years optimally. This research method includes Classroom Action Research with social maturity variables and outbound activity variables. The results obtained in the first cycle, namely the social maturity of children through outbound activities are still low not in accordance with the standard, namely an average of 65% and continued in the second cycle which has increased by 85%. With outbound activities, children who are initially timid in facing obstacles or barrier, become brave and even lose their fear after participating in outbound